PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI BANI ABBASIYAH KELAS VIII.2 DI SMP N 1 LAREH SAGO HALABAN - Yeni Pitri; Zulfani Sesmiarni; Rodi; Ashri Rahmatika Firdaus (CV. ADIBA ASIHA AMIRA, 2024)
This research is one of the assignments in the Daljab 3 Professional Teacher Education (PPG) program at the Sjech M. Djamil Djambek State Islamic University, Bukittinggi. Every teacher who takes part in this program must carry out Field Experience Practice (PPL) which is used to conduct research on problems in the learning process at school. With changes in the learning process during the pandemic, where learning was carried out online, it resulted in various problems in the implementation process. Limitations in the learning process result in student learning outcomes decreasing so that many students get grades below the Minimum Completeness Criteria (KKTP) This research aims to determine the increase in motivation and learning outcomes of students in Islamic Religious Education subjects using the Problem Based Learning learning model implemented in Blended Learning (Synchronous-Asynchronous). The research process was carried out in three cycles, previously taking action at the pre-cycle stage, each cycle includes 4 stages, namely: 1) planning stage, 2) implementation stage, 3) observation stage, 4) reflection stage. The results obtained from the implementation of the research show an increase in student learning outcomes, although not significant, this can be seen from the results obtained by students from working on student worksheets. It can be seen from the results of observations of student learning motivation in cycles I, II and III that there is an increase at each cycle meeting which can be seen on average in cycle I the average results of observations of student learning motivation were 57.14% to 60.71% in the cycle II and became 67.85% in cycle III, while the average results of the student motivation questionnaire in cycle I, the average student learning motivation was 57.14%, increased to 60.71% in cycle II and increased to 82.14% in cycle III. This is because several students have high enthusiasm in learning activities using the problem based learning model. In the initial activity when the first action was implemented in cycle I, the percentage of students who completed it was 55.5%. This shows that the expected KTTP percentage target has not been achieved. In cycle II, 59% of students completed. Meanwhile, the percentage of students who did not complete was 41%. During the implementation of cycle II, student learning outcomes showed an increase of 3.5%. Meanwhile in cycle III the average student completion rate was 67.85%. From cycle I to cycle III, not all students reached the KKTP, because there were some students who did not want to do the assignments. Thus, it can be concluded that the use of the Problem Based Learning learning model based on research results can actually improve learning outcomes in Islamic Religious Education subjects.